Emile Kok Kheng Yeoh y Hou Kok Chung (eds.), China and Malaysia in a Globalizing World. Bilateral Relations, Regional Imperations and Domestic Challenges, Kuala Lumpur, University of Malaya-Institute of China Studies, 2006, 273 pp. - Hernández Sánchez, Fernando Octavio (Estudios de Asia y África, 2010)
Emile Kok Kheng Yeoh y Hou Kok Chung (eds.), China and Malaysia in a Globalizing World. Bilateral Relations, Regional Imperations and Domestic Challenges, Kuala Lumpur, University of Malaya-Institute of China Studies, 2006, 273 pp.